Overexpression of TCERG1 as a prognostic marker in hepatocellular carcinoma: A TCGA data-based analysis - Yang, Pan; Liu, Huaifeng; Li, Yan; Gao, Qunwei; Chen, Xin; Chang, Junyan; Li, Yangyang; Chen, Shuran; Dong, Rui; Wu, Huazhang; Liu, Changqing; Liu, Gaofeng (Frontiers in Genetics, 2022)
Objective Transcription elongation factor 1 (TCERG1) is a nuclear protein consisted of multiple protein structural domains that plays an important role in regulating the transcription, extension, and splicing regulation of RNA polymerase II. However, the prognostic and immunological role of TCERG1 in human cancer remains unknown. In this study, we analyzed the expression of TCERG1 gene in hepatocellular carcinoma (HCC) patients, its clinical significance, and its possible prognostic value by bioinformatics. Methods RNA sequencing data and clinicopathological characteristics of patients with HCC were collected from TCGA and CCLE databases. The Wilcoxon rank-sum test was used to analyze the expression of TCERG1 in HCC tissues and normal tissues. The expression of TCERG1 in HCC cells were verified by qRT-PCR. Logistic regression, GSEA enrichment, TME, and single-sample set gene enrichment analysis (ssGSEA) were performed to explore the effects of TCERG1 on liver cancer biological function and immune infiltrates. TCERG1 co-expression networks were studied through the CCLE database and the LinkedOmics database to analyze genes that interact with TCERG1. Results The expression levels of TCERG1 in HCC patient tissues were significantly higher than in normal tissues. Survival analysis showed that high levels of TCERG1 expression were significantly associated with low survival rates in HCC patients. Multifactorial analysis showed that high TCERG1 expression was an independent risk factor affecting tumor prognosis. Co-expression analysis revealed that CPSF6 and MAML1 expression were positively correlated with TCERG1. GSEA showed that in samples with high TCERG1 expression, relevant signaling pathways associated with cell cycle, apoptosis, pathways in cancer and enriched in known tumors included Wnt signaling pathway, Vegf signaling pathway, Notch signaling pathway, MAPK signaling pathway and MTOR pathways. The expression of TCERG1 was positively correlated with tumor immune infiltrating cells (T helper 2 cells, T helper cells). Conclusion TCERG1 gene is highly expressed in hepatocellular carcinoma tissues, which is associated with the poor prognosis of liver cancer, and may be one of the markers for the diagnosis and screening of liver cancer and the prediction of prognosis effect. At the same time, TCERG1 may also become a new target for tumor immunotherapy.